Status of Anaemia in Different Stages Of Chronic Kidney Disease Patients (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Anemia is the universal complication of Chronic Kidney Disease (CKD) and reflects problem either in abnormally low production of RBC by the bone marrow or excessive haemolysis or blood loss. This study has been designed to observe the status of anaemia in different stages of chronic kidney disease patients. Materials and methods: It is a hospital based cross sectional comparative study. 100 patients of diagnosed case of chronic kidney disease admitted in the Department of Nephrology, Chittagong Medical College Hospital were selected as cases and 100 apparently healthy persons, age and sex matched were selected as controls. According to stages of CKD, cases were subdivided into three groups stage III, IV and V. Haemoglobin estimation was done manually by traditional method (Sahli’s acidhaematin method) in the Department of Physiology, Chittagong Medical College, Chittagong. Peripheral Blood Film (PBF) study also was performed in the department of Physiology, Chittagong Medical College, Chittagong. Data were analyzed by different statistical methods. Results: In our study, among the case group (100 patiens), we found that 5.5% are on CKD stage III, 21% on stage IV, 23.5% on stage V. And 50% (100 apparently healthy subjects) were taken as control. Here the mean (±SD) hemoglobin concentrations were 8.75(± 1.45) and 12.07(±1.77) gm/ dl of blood in case and control group respectively. Peripheral blood film study among the study groups showed that RBCs were found microcytic hypocromic in 69% of case and 20% control group. On the other hand RBCs were normocytic normocromic in 31% of case and 80% of control group. Again among the case group it was found that 54.5%, 71.4% and 70.2% of RBCs were found microcytic hypocromic in CKD patients with stage III, IV and V respectively. On the other hand RBCs were normocytic normocromic in 05%, 12% and 14% of CKD patients with stage III, IV and V respectively. Conclusion: The results of this study revealed that all the patients (100%) of the study were found anaemic and 69% CKD patients had microcytic hypochromic anaemia.JCMCTA 2017 ; 28 (2) : 59-63